Nanofiller Fibre-Reinforced Polymer Nanocomposites - Njuguna, James A. K.; Pielichowski, Krzysztof; Desai, S. (John Wiley & Sons, Ltd, 2008)
In this work, the technology of nano and micro-scale particle reinforcement concerning various polymeric fibre-reinforced systems including polyamides (PA), polyesters, polyurethanes, polypropylenes and high performance/temperature engineering polymers such as polyimide (PI), poly(ether ether ketone) (PEEK), polyarylacetylene (PAA) and poly p-phenylene benzobisoxazole (PBO) is reviewed. When the diameters of polymer fibre materials are shrunk from micrometers to submicrons or nanometers, there appear several unique characteristics such as very large surface area to volume ratio (this ratio for a nanofibre can be as large as 103 times of that of a microfibre), flexibility in surface functionalities and superior mechanical performance (such as stiffness and tensile strength) compared with any other known form of the material. However, nanoparticle reinforcement of fibre reinforced composites has been shown to be a possibility, but much work remains to be performed in order to understand how nanoreinforcement results in dramatic changes in material properties. The understanding of these phenomena will facilitate their extension to the reinforcement of more complicated anisotropic structures and advanced polymeric composite systems.